Challenges and opportunities in diagnosing and managing mild traumatic brain injury in rural settings - Jill Daugherty; Dana Waltzman; Shena Popat; Amy Horn Groenendaal; Maggie Cherney; Alana Knudson (James Cook University, 2022)
Introduction: There is some evidence to suggest that Americans living in rural areas are at increased risk for sustaining a traumatic brain injury (TBI) compared to those living in urban areas. In addition, once a TBI has been sustained, rural residents have worse outcomes, including a higher risk of death. Individuals living in rural areas tend to live farther from hospitals and have less access to TBI specialists. Aside from these factors, little is known what challenges healthcare providers practicing in rural areas face in diagnosing and managing TBI in their patients and what can be done to overcome these challenges. Methods: Seven focus groups and one individual interview were conducted with a total of 18 healthcare providers who mostly practiced in primary care or emergency department settings in rural areas. Providers were asked about common mechanisms of TBI in patients that they treat, challenges they face in initial and follow-up care, and opportunities for improvement in their practice. Results: The rural healthcare providers reported that common mechanisms of injury included sports-related injuries for their pediatric and adolescent patients and work-related accidents, motor vehicle crashes, and falls among their adult patients. Most providers felt prepared to diagnose and manage their patients with TBI, but acknowledged a series of challenges they face, including pushback from parents, athletes, and coaches and lack of specialists to whom they could refer. They also noted that patients had their own barriers to overcome for timely and adequate care, including lack of access to transportation, difficulties with cost and insurance, and denial about the seriousness of the injury. Despite these challenges, the focus group participants also outlined benefits to practicing in a rural area and several ways that their practice could improve with support. Conclusion: Rural healthcare providers may be comfortable diagnosing, treating, and managing their patients who present with a suspected TBI, but they also face many challenges in their practice. In this study it was continually noted that there was lack of resources and a lack of awareness, or recognition of the seriousness of TBI, among the providers' patient populations. Education about common symptoms and the need for evaluation after an injury is needed. The use of telemedicine, an increasingly common technology, may help close some gaps in access to services. People living in rural areas may be at increased risk for TBI. Healthcare providers who work in these areas face many challenges but have found ways to successfully manage the treatment of this injury in their patients.